Reseña de Couper-Kuhlen, E. y B. Kortmann (eds.) (2000), Cause, Condition, Concession, Contrast. Cognitive and Discourse, Perspectives. - Miñones, Laura (Pragmalingüística, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Couper-Kuhlen, E. y B. Kortmann (eds.) (2000), Cause, Condition, Concession, Contrast, Cognitive and Discourse, Perspectives.